The Decentralization Of Political Parties Through The Institutionalization Of The Local Political Parties - Muhammad Rifqinizamy Karsayuda (The Constitutional Court of the Republic of Indonesia, 2016)
The implementation of regional autonomy through Acts Number 23/2014 on Regional Government formulates the authority that can be maintained by local governments. One of the authorities’ is the political autonomy. The efforts to implement the political autonomy can be done through the institutionalization of local political parties. However, according to Indonesian Law, the institutionalization of local political parties is not regulated in the provisions of acts related to political parties. The legislation that regulates local political parties can be found only in Acts Number 11/2006 on Aceh Government and Acts Number 21/2001 on Special Autonomy for Papua Province. Therefore, this paper analyzes the theoretical, juridical and sociological reasons underpinned the idea of local political parties’ institutionalization. This research is a normative legal research which uses legal matter and acts to analyse the problems. This research finds strategies that is relevant to make local political parties institutionalized. There are five reasons to deliver local political parties in Indonesia based from this research. First, the theoretical foundation describes Indonesia as a country with federalism autonomy. Second, the constitutional juridical basis consists of two principles of the Constitution, namely the principle of the autonomy of the unitary state and the principle of equality and freedom of every citizen in governing. Third, The platform of sociological based on the fact that the choice of pluralistic Indonesian society is still diverse in many elections. Fourth, the historical background in the form of historical experience that in 1955 General Election and Local Election, there were several local political parties. Fifth, the comparative study in United Kingdom as a unitary state and Malaysia as a Federal State, which both have local political parties. The concept of local political parties that are relevant to be applied in Indonesia in the constitutional juridical perspective related to the decentralization of political parties can be built through four strategies. First, the local political party whose presence was based on pluralist paradigm which provides the idea that in a pluralistic society should be built a decentralized party system in order to sustain the plurality of society. Second, the local political party which drafted is a separate legal entity which is dichotomous from the national political parties as a legal entity. Third, local political party’s participation in elections only to the General Election and Local Elections for Legislative Elections candidates, the Provincial Representatives, Regency / City. Fourth, the formation mechanism, supervision and dissolution of local political parties are designed similar to national political process for parties as applicable today.